Hubungan Pengetahuan, Sikap, Dan Persepsi Terhadap Corona Virus Disease 2019 (COVID-19) Dengan Upaya Vaksinasi COVID-19 Pada Remaja Di SMK N 2 Rangkasbitung Banten Tahun 2022: Relationship of Knowledge, Attitudes, and Perceptions of Corona Virus Disease 2019 (COVID-19) with COVID-19 Vaccination Efforts in Adolescents at SMK N 2 Rangkasbitung Banten in 2022 - Ayuni, Widya (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: COVID-19 is a respiratory infectious disease caused by the SARS-CoV-2 virus. On March 2, 2020, Indonesia reported its first case of COVID-19. The case continues to increase in 34 provinces in Indonesia. In Indonesia, as of July 5, 2021, there were 2,284,084 confirmed cases. So far, as of August 5, 2021, the number of cases has reached 3,568,331. Banten Province has become an area with local transmission, as of August 5, 2021 cases have increased to 116,005 cases compared to July as many as 59,603 cases, which means there is a significant increase in the incidence rate in Banten Province. COVID-19 disease does not only attack adults but also affects children and adolescents. So that the readiness of teenagers and anticipatory efforts really need to be done to minimize the spread of COVID-19. One very possible way to prevent the spread of this virus is by developing a vaccine. The application of health protocols to break the chain of the spread of COVID-19, especially in adolescents, requires good knowledge, attitudes, and perceptions. Methods: This study uses a cross-sectional with a quantitative type of research conducted on adolescents at SMK N 2 Rangkasbitung Banten. Research subjects were selected by purposive sampling method. Results: The results of the Chi-Square test show that there is no significant relationship between knowledge of the Corona Virus Disease (COVID-19) and COVID-19 Vaccination Efforts, namely the p-value (0,153). There is a significant relationship between attitudes towards the Corona Virus Disease (COVID-19) and COVID-19 Vaccination Efforts, namely the p-value (0,032). And there is a significant relationship between perceptions of the Corona Virus Disease (COVID-19) and COVID-19 Vaccination Efforts, namely the p-value (0,000).  Discussion: There is no significant relationship between knowledge of the Corona Virus Disease (COVID-19) and COVID-19 Vaccination Efforts. However, there is a significant relationship between Attitudes and Perceptions of the Corona Virus Disease (COVID-19) with COVID-19 Vaccination Efforts in Adolescents at SMK N 2 Rangkasbitung Banten.